Women in Leadership : Contextual Dynamics and Boundaries, Second Edition. - Klenke, Karin (Emerald Publishing Limited, 2017)
The 2nd edition of this book, originally published in 2011, captures many significant recent developments and achievements in women's leadership. Women in virtually every context discussed in the book--politics, sports, business, technology, religion, military and international--have made dramatic gains in attaining leadership roles and positions.
Keywords: Leadership in women.; elektronické knihy; electronic books